Watching over the Sacred Boundaries of the Family. Study on the Standing Sentinels and Cultural Resistance to LGBT Rights - Righetti, Nicola (Italian Sociological Review, 2016)
The aim of this research is to present an exploratory study that examines some of the cultural assumptions on which the opposition to the social and legal recognition of homosexual marriage in Italy is based. These assumptions are based on a naturalistic anthropology which considers human nature, possibly created by God, structured exclusively in the complementary forms of male and female. Some recurring narrative elements which emerge from the social networks and from websites of a network of traditionalist movements, mainly linked to the Catholic area, are illustrated here, to propose, at the end, an interpretation, including with resort to some of the sociological categories devised by P.T. Berger and T. Luckmann. The naturalized ideas of humankind and the family seem to be the sacred foundations of the symbolic universe of the group; for this reason, the perception of any serious threat to the family is experienced by the members of the group as a serious profanation of the entire sacred order that is based on these foundations. Coherently with this, the forces identified at the origin of the profanation are shown as evil forces that seek to destroy the whole of humanity. The defence of the sacred values of the family therefore assumes the form of defence of cosmic order from the powers that seek to spread chaos.